DYNAMICS OF CHANGES IN THE LEVEL OF PERSONAL EXCITEMENT CAUSED BY THE EFFECT OF EMOTIONAL STRESS OF THE EXAM PROCESS IN 21-YEAR- OLD STUDENTS OF DIFFERENT TEMPERAMENT TYPES - Rustamova, T.V.; Jafarova, Sh.B.; Heydarli, L.A.; Alshanli, U.S. (World of Medicine and Biology, 2024)
One of the main causes of psychophysiological stress in students is exam stress, which often leads to neuropsychological disorders as the final result. The main goal of the present study was to reveal the age characteristics of the changes in the psychophysiological-excitement level caused by the emotional stress due to the examination process in students. Psychophysiological studies of different states of anxiety were conducted 2 months before the exam, 30 minutes before the exam and 30 minutes after the exam with 36 male students of 21 years of age having different typological features of the nervous system at Ganja State University. Practical health and voluntary engagement of the participants in researches were taken as important conditions. The analysis of the numerical average of the level of personal anxiety on ordinary days and the level after the exam shows that the personal anxiety was higher in young people after the exam. Thus, although the level of personal anxiety in 21-year-old students with four temperament types changed dramatically before and after the exam compared to their usual days, the difference between groups and temperament types was not statistically reliable and accurate in some cases.